O papel dos imigrantes japoneses na agricultura do norte do Paraná : o caso dos municípios de Assaí, Marialva e Uraí - Almeida, Ana Claudia Silva (2015)
Brazil received large numbers of immigrants in the last two centuries. The arrival of Japanese to the Brazilian space beginning a new phase in this process. The changes in the receiving society were significant and of great importance. After a few years of work in the country, a portion of these immigrants been able to acquire small farms, many of them in Paraná, particularly the northern part of the state. The entry of the Nipponese in Paraná land given to locations a different dynamic to the state context. The research developed here, sought to identify and analyze the influence of the Japanese immigrants in rural areas of north of Paraná and the contribution of these personages for agriculture in the municipalities of Assaí, Marialva and Uraí. To achieve the goals, quantitative data related to the farms were collected in the Paraná Institute of Technical Assistance and Rural Extension and the Brazilian Institute of Geography and Statistics, were also collected information through interviews with pioneers in the municipalities, representatives of agencies involved with agriculture in the municipality and with the producers of Japanese colony. Data analysis showed that the inclusion of modern agriculture production techniques in Paraná countryside, from the final years of the 1960s, linked to all the economic and social changes members of the so called modern package, strongly affected the rural organization of the three municipalities. Despite the impacts and changes promoted by the modernization of agriculture, the areas analyzed in the study have adapted to the new dynamics and created alternatives to the crisis. In Assaí and Uraí, diversification of agricultural products, work of Japanese colony, assured the permanence of small farms at the local context. In rural areas of Marialva the implementation of a different crop in the 1980s, the grape, activity hitherto developed exclusively in the Nikkei properties, managed to reverse the rural exodus in the municipality. Thus, the adoption by the Japanese of new agricultural techniques, the introduction of new crops and selection of existing crop species in Brazil, contributed to the development and strengthening of agricultural areas of the north of Paraná.